Attitudes Towards E-Learning (Version 2.X): What Do Students Think Now? - Loh, Hwee Kuen Claire; Kingshott, Russel; Wong, David (Australian and New Zealand Marketing Academy, 2012)
The body of literature investigating issues relating to e-learning is quickly growing as many scholars in this area seek to explain how new technologies such as social media and other Web 2.0 tools may be incorporated into both online and ‘offline’ modes of learning. The extent of recent literature published in the last five years in this area had largely focussed on how successful pedagogical techniques incorporating these new technologies may be used (e.g., English and Duncan-Howell, 2008; McLoughlin and Lee, 2008), and how these technologies transform the way universities interact with their students (e.g., Wong, 2012). In the race towards defining these mechanics, a fundamental gap emerges – few researchers have taken a step back to measure how students’ perceptions have evolved with this new way of learning. This paper addresses this gap by revisiting a fundamental question in marketing – what do our ‘customers’ think now? The results show that while interactivity and feedback were primary concerns of students in earlier studies on e-learning (e.g., Kriger, 2001), current concerns of students are focussed on flexibility for self-paced learning, costs savings, issues in self-motivation, and concerns about the limitations of technology in fostering teamwork for group assessments.